MANAJEMEN STRATEGIS PENINGKATAN AKREDITASI: STUDI KASUS PRODI TATA KELOLA SENI - Gunawan, Indra; Widiastuti, Nur (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to identify the factors influencing the accreditation ranking of the Program Studi S-1 Tata Kelola Seni (Prodi TKS), Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Yogyakarta, which is currently rated as "Baik Sekali", and to formulate strategic steps to elevate the ranking to "Unggul". Employing a qualitative research approach, data were collected through document analysis, in-depth interviews, and participatory observation. The findings reveal that the current accreditation status is influenced by several critical components, including the number and qualifications of Permanent Lecturers of the Study Program (DTPS) and the average study duration of graduates. Prodi TKS has made efforts to increase the number of qualified DTPS and to reduce the time students take to complete their studies. This research contributes theoretically to the field of higher education management by presenting a conceptual framework for the quality assurance process in arts-based study programs. Practically, this study provides strategic insights for policymakers and academic leaders in improving accreditation outcomes through targeted resource allocation, strengthening institutional collaboration, and monitoring performance. The proposed improvement strategies, including strengthening synergies between study programs, faculties, institutions, and external partners, can serve as a model for similar study programs focused on improving quality and accreditation rankings.